Context-dependent effects of the loss of Spartina alterniflora on salt marsh invertebrate communities. (20th September 2015) - McFarlin, Caroline R.; Bishop, T. Dale; Hester, Mark W.; Alber, Merryl
Abstract: Sudden dieback of the salt marsh grass Spartina alterniflora during 2000–2002 transformed once-vegetated areas to bare sediment in coastal Georgia and Louisiana. We investigated the effects of losing this foundation species on habitat provisioning for benthic epifauna, macroinfauna, and meiofauna in these distinct geographical regions. In GA, significant shifts in invertebrate community assemblages were observed between bare and reference (vegetated) plots, with abundances of all invertebrate groups and the diversity of macroinfauna lower in bare plots. In LA, community assemblages overlapped considerably in dieback and reference plots. Although epifaunal snails were significantly decreased in dieback plots, meiofauna were unexpectedly increased . Other invertebrates did not differ between plots. Supplemental transplanted plots allowed for direct evaluation of stem density effects on invertebrates. Stem density predicted abundances of all invertebrate groups in GA, and was positively correlated with increased soil moisture. In LA, elevation and soil moisture were good predictors of infauna but were not related to stem density. Differences between the states suggest that S. alterniflora may not provide equivalent ecosystem services in all salt marshes. Additional disturbances (drought, GA; hurricanes, LA) decreased infaunal density and taxon richness in 2008. However, in both states the reduction of macroinfauna was larger in bare than reference areas, suggesting that vegetation protected against further disturbance. Our results suggest that the role of S. alterniflora is context-dependent both in terms of geographic setting and the specific ecosystem service under consideration. Graphical abstract: